SWAT Special Issue published in IJABE - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2015)
The Editor-in-Chief of IJABE is pleased to publish this SWAT special issue including one editorial overview and ten research papers, which will be open access to the full-text of each paper. Brief summaries of the process of collecting and reviewing the submitted papers for this SWAT special issue are provided. Acknowledgements were given to all the editors, reviewers and authors, with special thanks to the lead guest editor Dr. Philip Gassman for his leading role and great job, including a complete listing of associate editors. We have published this special issue in both print and online electronic version. The online version will provide open access to the full text of each paper free of charge and free of most of copyright restrictions. Keywords: IJABE, SWAT special issue, special columnDOI: 10.3965/j.ijabe.20150803.editorialCitation: WangY K. Editorial: SWAT Special Issue published in IJABE. Int J Agric & Biol Eng, 2015; 8(3): 01－02.